'Punching above our weight': industry visibility and community engagement in rural and regional film festivals. Issue 4 (2nd October 2022) - Van Hemert, Tess; Ellison, Elizabeth
ABSTRACT: In Australia, the most visible film festivals are clustered around urban centres, yet there is a flourishing network of film festivals outside of major cities. In the state of Queensland, the festivals in regional and rural areas provide crucial visibility for the industry, local community and emerging filmmakers. Following the growth in film festival scholarship, and research on global digital distribution, the impetus for this research was to examine why so many film festivals continue to operate in Queensland. Using a broader mapping project as context, this article examines how the specificity of place shapes the identity of two case study festivals, their audience, and connection to community. The research identifies three key concerns: the distinctions between regional and metropolitan festivals; the duality of these festivals as both inward and outward facing events; and the challenges of viability that face the future of Queensland's festival sector. In 2020, the COVID-19 global pandemic caused further disruption to the national and international screen industries. While this upheaval continues to affect the screen industry, it is important to understand the role that film festivals already play in cultivating and sustaining local audiences and communities, and consider strategies to support their ongoing viability.